Glycerolysis of Palm Oil Using Copper Oxide Nanoparticles Combined With Homogeneous Base Catalyst - Huei, Ruey Ong; Khan, Maksudur R.; Ridzuan, Ramli; R. M., Yunus; Rahman, Md. Wasikur (Royal Society of Chemistry, 2016)
In the present work, a new catalyst system composed of copper oxide nanoparticles (CuO-nano) along with a conventional homogeneous base catalyst (NaOH) for the glycerolysis of palm oil to produce monoglycerides (MG) was proposed. CuO-nano was synthesized in glycerol and directly used in the glycerolysis reactions, which formed a pseudo-homogeneous system. The production of MG and diglycerides (DG) from oil was monitored by using 1H-NMR, 13C-NMR and HPLC. When compared with the conventional NaOH catalyst, CuO-nano used alone showed less activity, but adding NaOH to the CuO-nano exhibited a synergistic effect by increasing the MG yield significantly. The oil conversion, MG and DG yield were achieved at 95, 71 and 24%, respectively, for the new catalyst system composed of CuO-nano and NaOH. The mechanism of the glycerolysis reaction over CuO-nano and NaOH was elucidated.